Textural and petrological studies of anatexis and melt transfer in the Himalayan Orogen - Dyck, B (2016)
Mineral textures, preserved in the metamorphosed sedimentary sequences that are exposed in orogenic hinterlands, are crucial to understanding the architecture and evolution of collisional mountain belts. In this thesis the textural record of anatexis and melt transfer in the Himalayan metamorphic core is decoded and the controls that these processes exert on the tectonic evolution of the Himalaya are explored. The problem is divided into two parts, corresponding to variations in protolith lithostratigraphy: melt source – the pelitic region where melt was first generated, and melt sink – the psammitic region where melt accumulated and crystallised. Dehydration melting of muscovite has long been recognized as a critical reaction for the generation of anatectic melt in the Himalaya, but a textural understanding of how this reaction progresses is limited by the inherent difficulties in identifying specific reaction products. Using samples collected from the Langtang area in central Nepal, a mechanistic model for muscovite dehydration melting was constructed, and a set of textural criteria were developed, which were used to distinguish peritectic K-feldspar from K-feldspar grains formed during melt crystallisation. Melt is transferred from the source to the sink in two stages: firstly along a pervasive network of mineral grain boundaries, and secondly via a channelised network of sills and dykes in the melt sink where it solidified as leucogranite. Variation in the primary mineral assemblage and appearance of leucogranite bodies reflect the degree of interaction that occurred between the melt and metasedimentary country rock, rather than a change in primary melt composition. The modal proportion of K-feldspar in the melt source requires vapour-absent conditions during muscovite dehydration melting and leucogranite formation, indicating that the generation of large volumes of granitic melts in orogenic belts is not necessarily contingent on an external source of fluids. The crystallisation of hydrous minerals in leucogranite consumes <15.5 % of water released by the breakdown of muscovite. These results indicate that anatexis efficiently dehydrates the middle crust and suggests that the continents have limited potential to store water over geological time.